Mediating Effect Of Locus Of Control On The Causal Relationship Between Students’ Perceived Teachers’ Expectancy And Self-Esteem - Kususanto, Prihadi (2012)
This mixed method study is looking at the mediation effect of Locus of control on the causal relationship between students’ perceived teachers’ expectancy and their self-esteem in the schools where Between Class Ability Grouping is practiced. The existence of correspondence bias among the teachers in such schools is also investigated. A total of 795 form two (year 8) students (446 low achievers and 349 high achievers) and 72 teachers from five secondary schools in the state of Penang were selected via purposive sampling method to participate in the quantitative part of this study. 10 teachers and 7 students from were taken from the sample in order to participate in the qualitative part of this study. Quantitatively, self-esteem was measured by the Rosenberg Self-Esteem Scale (Rosenberg, 1965), while Locus of Control was measured by using Internal Control Index (Dutweiller, 1984), and Students’ perceived teachers’ expectancy is measured by using Scales of Perceived Teachers’ Expectancy (Prihadi, 2009). Scale of Teachers’ Expectancy was developed in order to collect the data about teachers’ expectancy towards the students. All scales were translated into the Malay language and internal consistency reliability scores (Cronbach’s alpha) were found to be above 0.6 for all scales. Open-ended interviews to the students and teachers were conducted in order to collect the qualitative data. Results showed that students from low-performers’ classes had their internal Locus of Control mediates the influence of their perceived teachers’ expectancy on their self-esteem; in other words, their self-esteem would not be influenced by their perception of teachers’ expectancy if they have internal Locus of Control. However, mediation effect was not shown among high-performer students. This study also discovered that correspondence bias occurred among teachers, which means that teachers developed different expectancy towards high and low achiever students without any further consideration; they expect high-achievers to be willing to improve their achievement and low-achievers are expected to be involved in disciplinary problems. Some meaningful themes emerged during the qualitative data analyses and played their roles in explaining the phenomenon even deeper. The themes are namely reciprocal envy between high and low achievers, pressure from the school managements’ goals, and the involvement of tuition centers.